Connecting the English Class to the Internet of Things - Coanca, Mariana (European Scientific Journal, ESJ, 2018)
It goes without saying that the World Wide Web drives learners/students to become more autonomous as it offers an array of tools that cater for students’ diverse needs and learning styles. This paper connects the teaching and learning English for Specific Purposes to the ecosystem of the Internet of Things. More precisely, we explore the concept of Internet of Things and its characteristics and address seminal questions about its role in education. After analyzing the findings, we focus on the educative value of digital technologies to our practice as language educators. Drawing on our experience of teaching with web-based tools, we showcase a lesson plan that increased students’ motivation, interaction and engagement. The paper concludes that teaching will definitely become more and more dependent on technology but policy makers need to consider proactively the use of digital technologies as pedagogical tools and to collaborate extensively with educators and technology experts/developers to create innovative strategies for education.